2013
DOI: 10.1002/jcb.24545
|View full text |Cite
|
Sign up to set email alerts
|

AKT primes snail‐induced EMT concomitantly with the collective migration of squamous cell carcinoma cells

Abstract: In this study, we found that wounding of a confluent monolayer of squamous cell carcinoma (SCC) cells induced epithelial-mesenchymal transition (EMT) specifically at the edge of the wound. This process required the combined stimulation of TGFβ, TNFα, and PDGF-D. Such a combined cytokine treatment of confluent monolayers of the cells upregulated the expression levels of Snail and Slug via PI3K. The PI3K downstream effector, AKT, was dispensable for the upregulation of Snail and Slug, but essential for enabling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…The phospho-AKT level is a classic indicator to evaluate AKT activity (40). Okui et al demonstrated that the PI3K/AKT signaling pathway is closely associated with EMT induction and human tumor development (41). In the present study, IL-8 stimulation could noticeably enhance the phosphorylated AKT levels as well as the motility and invasiveness of RCC cells.…”
Section: Discussionsupporting
confidence: 55%
“…The phospho-AKT level is a classic indicator to evaluate AKT activity (40). Okui et al demonstrated that the PI3K/AKT signaling pathway is closely associated with EMT induction and human tumor development (41). In the present study, IL-8 stimulation could noticeably enhance the phosphorylated AKT levels as well as the motility and invasiveness of RCC cells.…”
Section: Discussionsupporting
confidence: 55%
“…It has also been reported that Akt, which acts downstream of PI3K, is very important for upregulation of Slug and Twist, two transcriptional factors that initiate EMT. 33 Previously, Severson et al 34 showed that JAM-A dimerization promotes Ras-proximate-1 (Rap1)-GTPase activation, beta 1 integrin upregulation and enhances cell migration, one of the hallmarks of EMT. Mandell et al 35 confirmed that JAM-A regulates epithelial cell morphology by modulating the activity of the Rap1-GTPase.…”
Section: Jam-a a Member Of The Junctional Adhesion Molecule Family mentioning
confidence: 99%
“…Cell cycle is verified to be modulated by many cell-cycle promotors and inhibitors, such as Rb and cyclin D1 in the regulation of the G1/S transition. 39 , 40 Compared with the NC-transfected cells, the protein and mRNA expressions of p21 Cip1 and p27 Kip1 , 2 cell-cycle inhibitors, were increased in miR-495-transfected cells. However, the expression of cyclin D1, a cell-cycle promoter, was decreased in miR-495-transfected cells.…”
Section: Resultsmentioning
confidence: 98%